How do family firms balance economic and non-economic goals: from symbiosis to competition - Zhang, Wei; Wu, Bingde; Chen, Ling; Zhu, Jian-an; Chen, Shihui (Frontiers in Psychology, 2025)
IntroductionThe coexistence of non-economic and economic goals is a prominent feature of family firms. However, does the pursuit of non-economic goals necessarily imply that the economic goals should be sacrificed? Our research addresses this question by exploring the symbiotic or competitive relationship between non-economic goals and economic goals in Chinese family firms, and the moderating effect of firm size and firm age.MethodsBased on 2877 firm-year observations of Chinese listed family firms from year 2009 to 2019, this paper examines the relationship between non-economic goals (measured by family management) and economic goals (measured by firm performance). A panel data fixed-effects regression model was employed for the primary analysis. To further ensure the credibility of our conclusions, we performed several robustness tests, such as utilizing alternative variable measurement and conducting an endogeneity test.ResultsThe empirical analysis revealed an inverted U-shaped relationship between family management and firm performance, where the extent to which non-economic goals are positively related to economic goals up to a point, after the turning point it becomes negative, which shows the trend from symbiosis to competition. Furthermore, as firm age increases and firm size expands, the inverted U-shaped curve flattens, and the turning point shifts to the right.DiscussionEmploying a willingness and ability perspective, this research contributes to the socioemotional wealth (SEW) framework by offering insights into the dynamic interplay between economic and non-economic goals in Chinese family firms. Moreover, by examining Chinese family firms influenced by Confucian values, our study highlights the importance of cultural context for generalizability, while simultaneously enriching SEW discourse and fostering avenues for cross-regional comparative analysis.